Case Against Manifesto - J. D. Crossan (Law Text Culture, 2000)
Detailed cases are not nearly as dramatic as sweeping manifestos but case-laws often effect what clarion-calls can only proclaim. Indeed, sometimes the sheer radical beauty of the manifesto can so exhaust the human imagination that nothing else happens afterwards. Christian commentators, for example, will often exalt Gospel over Law, New Testament over Old Testament, and even Christianity over Judaism on exactly that comparison. They may cite the Pauline manifesto in Galatians 3: 28 asserting that, "there is no longer Jew or Greek, there is no longer slave or free, there is no longer male and female; for all of you are one in Christ Jesus". The basic human differences, hierarchies, and discriminations of race/religion, class, and gender are declared irrelevant, at least for Christians. What could be more ideal and magnificent? But what exactly are its external effects and social repercussions? Is it all just internal and spiritual; meaning that we are all the same inside, that our souls are unraced, unclassed, and ungendered in the sight of God? And, if that is all it means, is that enough?